Analisis Pengaruh Akuntabilitas, Transparansi dan Sistem Pengendalian Intern terhadap Kinerja Pemerintah Daerah (Study Empiris pada Organisasi Perangkat Daerah (OPD) di Provinsi Jambi) - Abdul Haris; Ratih Rosita; Asrini Asrini (Universitas Batanghari Jambi, 2022)
This study aims to obtain empirical results, namely the Effect of Accountability, Transparency and Internal Control Systems on Local Government Performance (Case Study of OPD Dinas Jambi Province). Respondents in this study were service heads, financial administration officials, and treasurers in 19 Jambi provincial offices. Of the 57 questionnaires that were distributed, 51 respondents were obtained which could be included in data processing. The sampling technique in this study used the purposive sampling method. The data analysis technique uses the Multiple Linear Regression Analysis Technique. The software used for data processing is SPSS version 22. The statistical analysis used in this research is the Validity Test, Reliability Test and Classical Assumption Test. The results of testing the hypothesis are as follows: First, Accountability, Transparency and Internal Control Systems Affect Local Government Performance. Both Accountability Affects Regional Government Performance. Third, transparency has no effect on local government performance. The Four Internal Control Systems Influence Regional Government Performance.